Determination of Microbiological Quality of Bread and Sanitation Conditions of Local Bakeries in Aliero Town, Kebbi State - Muhammad Muhammad, Shamsudeen; Ibrahim Galadima, Samira (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2022)
Several variations and changes can occur during bread processing and storage that affect the quality and safety characteristics and acceptability of the bread. The study aimed to assess the microbiological quality of bread and the hygienic conditions of local bakeries in Aliero, Kebbi State. A total of 16 bread samples were obtained (3 from each bakery). Data on socio-demographics and sanitary conditions were collected through interviews and an observation checklist. Standard microbiological methods were used to enumerate, isolate and identify bacteria and fungi. The result of sanitary conditions shows that four bakeries (66%) use boreholes as a source of water supply, two (33%) use well and none of them use pipe borne. In addition, zero (0%) use a flush system of latrine, 66% have a pit latrine while 33% have no latrine facility. All (100%) have stored refuse also and adequately use open surfaces/ditch as a waste disposal method. The result of the study indicated the mean bacterial count (CFU/g) range is 7.4×105- 14.4x105, while the mean fungal count (CFU/g) range is 9.0×103- 1.1×103. Isolated bacteria include Escherichia coli (29.4%), Pseudomonas spp. (14.7%), Proteus spp. (20.6%), and Bacillus spp. (35.3%). Penicillium spp. (44%), Aspergillus spp. (8%), Rhizopus spp. (28%), Fusarium spp. (20%) were the fungi isolated and identified. Several types of pathogenic and non-pathogenic microorganisms were found to contaminate bread samples in the bakeries. Therefore, relevant regulatory agencies should ensure compliance with the guidelines and requirements for bread manufacturing. In addition, Educational programs have been recommended.